The use of enhancement material in grounding system: a review - Aizat Azmi; Noor Azlinda Ahmad; Lau Kwan Yiew; Z. Abdul-Malek (Institute of Advanced Engineering and Science, 2019)
This paper reviews the improvement of grounding impedance in grounding system by means of enhancement materials. Various enhancement materials for the past 20 years will be reviewed according to their advantages and disadvantages, followed by a focus on the technique for proper measurement set up based on the standard. In addition to that, the condition of enhancement materials under high voltage exposure is reviewed. Many researchers claim that soil resistivity, moisture content, and surrounding environment are the most contributed to the grounding system specifically on the grounding impedance. Hence, the utilization of enhancement materials is essential in order to maintain the grounding system performance.